The Relationship among Self-Efficacy, Mathematical Concepts Understanding, Creative Thinking Skills, Mathematical Problem-Solving Skills, and Mathematics Learning Outcomes - Khathibul Umam Zaid Nugroho; Eddy Izwanto; Wahyu Widada; Norma Alias; Abdurrobbil Falaq Dwi Anggoro; Dewi Herawaty; Rahmat Jumri; Shadaqnas Dewarif Tri Anggoro (Edumatika, 2023)
The proficiency of students in mathematical problem-solving skills is believed to be shaped by factors such as mathematical concepts understanding, creative thinking skills, and self-efficacy. This research endeavors to investigate the interplay among self-efficacy, mathematical concepts understanding, creative thinking skills, problem-solving skills, and mathematics learning outcomes. Employing a survey approach, the study encompasses all ninth-grade students in Central Bengkulu, Bengkulu, Indonesia, with a sample of 100 students selected through proportional stratified random sampling. Data collection involves Likert scale instruments for self-efficacy, along with tests for mathematical concepts understanding, creative thinking skills, and problem-solving skills. Path analysis techniques are applied for data analysis. The findings of the research indicate that mathematical concepts understanding, creative thinking skills, and problem-solving skills collectively exert a positive influence on mathematics learning outcomes. Additionally, it is demonstrated that self-efficacy, understanding mathematical concepts, and creative thinking skills collectively contribute positively to problem-solving skills. Furthermore, the research reveals a direct positive influence of self-efficacy on both mathematical concepts understanding and creative thinking skills.